2012
DOI: 10.5430/jnep.v2n2p80
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from active surveillance to active treatment for prostate cancer: A qualitative analysis

Abstract: Active surveillance (AS) has been an option for prostate cancer management for many years. However, only about 10% of clinically appropriate prostate cancer patients undergo AS. The reasons for the low selection and adherence to AS are unknown. The purpose of this qualitative study was to examine the reasons why men convert from AS to active treatment. Known converters from AS to active treatment were identified through the PI's prior study with this population and participating urologists. A purposive sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Twenty‐three papers were included, 20 quantitative and 3 qualitative . Nine were longitudinal with a follow‐up period ranging from 9 months to 3 years .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐three papers were included, 20 quantitative and 3 qualitative . Nine were longitudinal with a follow‐up period ranging from 9 months to 3 years .…”
Section: Resultsmentioning
confidence: 99%
“…Four of the 9 longitudinal studies had follow‐up response rates of >70%, whereas others reported more conservative follow‐up response rates of <60% . Fourteen were cross‐sectional, with time since diagnosis ranging from 2 months to 136 months . Six papers referring to WW, yet providing definitions for AS, ie, not palliative care, were included .…”
Section: Resultsmentioning
confidence: 99%
“…31 Our findings are broadly consistent with previous quantitative studies 9-13 but appear to differ from some previous qualitative research that reports persistent worry, altered social activities, and greater psychological needs in men on AS/WW. [15][16][17][18] These studies were, however, based on much smaller samples of men on WW (less than 10 participants), 15,16 those who switched from AS to AT 18 or focused on men closer to diagnosis. Men in our sample were 18 to 42 months post diagnosis, and it is possible those initially on AS experiencing greater anxiety had opted for AT within the study time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews of quantitative studies suggest that quality of life and psychological well‐being in men on AS/WW are generally good and comparable with, or better than, men who received AT. However, evidence from qualitative studies suggests that men on AS/WW may struggle with anxiety . Further exploration is needed to understand how men adjust to being on AS/WW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation